Analisis Proses Produksi terhadap Kualitas Bakpia dengan Metode Failure and Effect Analysis (FMEA) pada Usaha Mikro Kecil dan Menengah (UMKM) - Bakti Rajainal Akbar; Mohammad Muslimin; Anita Anita (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the risk of failure in the bakpia production process in the Micro, Small, and Medium Enterprises (MSMEs) sector using the Failure Mode and Effect Analysis (FMEA) method. The research is motivated by inconsistencies in product quality due to unstandardized production processes, limited resources, the use of simple equipment, and weak quality control. The research method used is a descriptive qualitative approach with data collection through observation, interviews, and documentation. Each production stage is analyzed to identify potential failures, their causes, and their impact on product quality. Risk assessment is carried out based on severity, occurrence, and detection parameters to obtain a Risk Priority Number (RPN) value. The results show that several production stages have dominant failure risks that affect product quality. The FMEA method has proven effective in determining risk priorities and serves as a basis for developing improvement proposals to minimize product defects and improve the quality and efficiency of the production process in a sustainable manner.